The Price of Appearances: Materialism in Maupassant’s The Necklace and Modern Consumer Culture - Bakri, Fitriani; Hasbi, Muhammad; Halim, Abdul (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
This study aims to explore the readers’ reception on The Necklace short story based on Hall’s reception theory. Employing descriptive-qualitative research design, the study focuses on Hall’s three main reading positions: the dominant-hegemonic, in which the reader decodes the message as intended by the author; the negotiated, where the reader partly accepts and partly resists the message; and the oppositional, where the reader rejects the encoded message entirely. Data were collected through two main instruments: students’ intellectual diaries (reflective journals) and classroom discussions. Data analysis follows Braun & Clarke’s thematic analysis. The findings of this study provide a nuanced understanding of how university students interpret Maupassant’s The Necklace in relation to materialism and contemporary consumer culture, viewed through the lens of Hall’s reception theory. The students’ responses, categorized into dominant-hegemonic, negotiated, and oppositional readings, reveal the multiplicity of interpretive positions shaped by ideological alignment, personal experience, and sociocultural context. This study shows that The Necklace story remains a powerful and relevant story, offering rich opportunities for critical engagement and reflection in the classroom. It becomes evident that literary texts are not static but dynamic sites where meaning is contested and reinterpreted across time and space. This study has shown that literature remains an essential tool for fostering critical thinking and for engaging students with the social, cultural, and ideological issues of their time.